The work of a student to solve the equation 4(2x − 4) = 8 + 2x + 8 is shown below:

Step 1: 4(2x − 4) = 8 + 2x + 8
Step 2: 6x − 8 = 16 + 2x
Step 3: 6x − 2x = 16 + 8
Step 4: 4x = 24
Step 5: x = 6

In which step did the student first make an error and what is the correct step?

Step 2; 8x − 4 = 2(6 + x + 6)
Step 2; 8x − 16 = 16 + 2x
Step 3; 6x − 2x = 16 − 8
Step 3; 6x + 2x = 16 + 8

Respuesta :

In step two. If we look on the left side of the equation in the first step, it reads 4(2x-4). When a number is multiplying an expression in brackets, we have to multiply every term in the brackets by the number in front of the brackets. In this case, it would be 4*2x + 4*(-4), which is 8x - 16. So the correct option would be the second (8x-16=16+2x) (the right side of the eqtn was 8+2x+8 and if we combine like terms we get 16+2x)
dd50

Answer:

The answer is B. Step 2; 8x − 16 = 16 + 2x

Hope This Helps!